Human Bocavirus Capsid Structure: Insights into the Structural Repertoire of the Parvoviridae - Gurda, Brittney L. (American Society for Microbiology (ASM), 2010)
Human bocavirus (HBoV) was recently discovered and classified in the Bocavirus genus (family Parvoviridae, subfamily Parvovirinae) on the basis of genomic similarity to bovine parvovirus and canine minute virus. HBoV has been implicated in respiratory tract infections and gastroenteric disease in children worldwide, yet despite numerous epidemiological reports, there has been limited biochemical and molecular characterization of the virus. Reported here is the three-dimensional structure of recombinant HBoV capsids, assembled from viral protein 2 (VP2), at 7.9-Å resolution as determined by cryo-electron microscopy and image reconstruction. A pseudo-atomic model of HBoV VP2 was derived from sequence alignment analysis and knowledge of the crystal structure of human parvovirus B19 (genus Erythrovirus). Comparison of the HBoV capsid structure to that of parvoviruses from five separate genera demonstrates strong conservation of a β-barrel core domain and an α-helix, from which emanate several loops of various lengths and conformations, yielding a unique surface topology that differs from the three already described for this family. The highly conserved core is consistent with observations for other single-stranded DNA viruses, and variable surface loops have been shown to confer the host-specific tropism and the diverse antigenic properties of this family.